ENHANCED TRANSDERMAL PERMEABILITY OF DICLOFENAC DIETHYLAMINE USING NANOEMULSION VEHICLE (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The transdermal delivery of Diclofenac diethylamine has attracted considerable interest in recent years due to a lot of significant properties. Transdermal delivery system exhibits very poor permeation through the skin. Thus, an attempt was made to enhance the transdermal permeability of drug using nanoemulsion as vehicle. The main objective of this study was to develop a potential of nanoemulsion formulation for transdermal delivery of Diclofenac diethylamine for inflammatory disease. Transdermal patches were prepared using solvent evaporation technique. In this investigation, the transdermal patches (control) and nanoemulsion containing transdermal patches were prepared, compared and characterized for different physicochemical parameters (moisture content, moisture uptake folding endurance, in-vitro drug release). The optimized batch was also subjected for in-vivo anti-inflammatory study, pharmacokinetics (Cmax, Tmax and AUC) study and skin irritation study. The physical evaluation indicated that the prepared batches were smooth, flexible and translucent. The transdermal patch having 1:5 ratio of polyvinyl pyrrolidone and ethyl cellulose, exhibited a 1.7 fold increase in skin permeation compare to Diclofenac diethylamine patch. Nanoemulsion containing transdermal patch showed a significant increase in permeation parameters such as steady state flux (Jss); 0.061 mgcm-2hr-1 and permeability coefficient (Kp); 0.025 cmhr-1, when compared to the control. The mean Cmax of drug for optimized transdermal patch (TD) and nanoemulsion transdermal patch (NETD) was 2.56µg/ml and 3.42µg/ml, respectively. The in-vivo studies revealed a constant plasma concentration of drug for long period. Thus, results indicated that the nanoemulsion containing transdermal patches can be a promising tool for enhancing the percutaneous delivery of Diclofenac diethylamine.